Comparison of Pregnancies between Perinatally and Sexually HIV-Infected Women: An Observational Study at an Urban Hospital - Martina L. Badell; Alisa Kachikis; Lisa B. Haddad; Minh Ly Nguyen; Michael Lindsay (Hindawi Limited, 2013)
As perinatally HIV-infected (PHIV) women reach reproductive age, there is an increasing number who become pregnant. This is a retrospective cohort study of HIV-infected women who delivered from June 2007 to July 2012 at our institution. Maternal demographics, HIV characteristics, and obstetric and neonatal outcomes were compared. 20 PHIV and 80 SHIV pregnancies were reviewed. The groups had similar CD4+ counts, prevalence of AIDS, and use of antiretrovirals (ARV) at initiation of obstetrical care. PHIV women were significantly more likely to be younger, have a detectable viral load (35% versus 74%, ), and have HIV-genotype resistance (40% versus 12%, ) than the SHIV women. The median gestational age at delivery (38 weeks) and rates of obstetrical and neonatal complications were similar between the groups. While the overall rate of cesarean delivery (CD) was similar, the rates for CD due to HIV were higher in the PHIV group (64% versus 22%, ). There was one case (5.3%) of mother-to-child transmission in the PHIV group versus two cases (2.6%) in the SHIV group. In our population, PHIV pregnant women have a higher rate of HIV-genotype resistance and higher rate of detectable viral load leading to a higher rate of CD secondary to HIV.